The effect of transformational leadership and well-being on performance of soccer players: an inclusive model - Yildirim, S.; Koruç, Z. (The Sport Psychologist, 2021)
The current study focuses on the effect of transformational leadership on athletes` performance in the mediation of psychological need satisfaction, burnout, competition anxiety, life satisfaction, and positive-negative affect. The sample consisted of 391 soccer players aged between 16 and 20 years. Six scales were used in this study: Multifactor Leadership Questionnaire, Needs Satisfaction Scale, Athlete Burnout Measure, Satisfaction with Life Scale, Positive and Negative Affect Scale, and Sport Competition Anxiety Test. The method of Vallerand was preferred to measure performance, and structural equation modeling was employed to analyze data. The model data fit was also verified. It was found that the transformational leadership behaviors of coaches signally influence athletes` performance either directly or indirectly. From another perspective, increasing the psychological health or well-being of athletes has important effects on sport performance.